2020
DOI: 10.1002/app.49569
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear influences of process parameters on mechanical properties of physically foamed, fiber‐reinforced polypropylene parts

Abstract: The importance of foam injection molded components in industrial applications increases, above all driven by sustainability concerns. In practice, their applicability almost exclusively depends on their mechanical behavior, which is still difficult to predict based on their microstructure. This work aims to present an approach based upon phenomenological observations. From a processing perspective, the objective is to describe the direct processing‐properties‐relationship. Therefore, this work focuses on the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…The appropriate fiber orientation, documented in an earlier article [ 22 ] and confirmed by additional SEM and FEM analysis, is also of great importance for the obtained properties. Therefore a slight decrease in mechanical properties was observed, which is in agreement with other researches [ 12 , 14 , 17 ]. It has been shown that the MuCell ® technology enables the manufacturing of thick-walled polyamide moldings with strength properties similar to those of aluminum alloys.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The appropriate fiber orientation, documented in an earlier article [ 22 ] and confirmed by additional SEM and FEM analysis, is also of great importance for the obtained properties. Therefore a slight decrease in mechanical properties was observed, which is in agreement with other researches [ 12 , 14 , 17 ]. It has been shown that the MuCell ® technology enables the manufacturing of thick-walled polyamide moldings with strength properties similar to those of aluminum alloys.…”
Section: Discussionsupporting
confidence: 92%
“…However, reinforced polyamide material is a popular technical polymer used, among others, in the automotive industry and other important market segments. Unfilled [ 15 , 16 ] or glass fiber reinforced polyolefins [ 17 , 18 , 19 ], as well as PP blends [ 15 ], are usually applied in scientific tests. A wall thickness of examined molded parts with standard and original geometry do not exceed 4 mm in most cases.…”
Section: Introductionmentioning
confidence: 99%
“…According to the classical nucleation theory, the increased melt temperature was also beneficial to improve the cell nucleation rate and thus achieve a finer cell structure [ 33 , 34 ]. As shown in Figure 2 c,d, the cell structure was improved when the temperature was increased by 20 °C.…”
Section: Resultsmentioning
confidence: 99%
“…Polymers and Fillers Molded Part Thickness, mm [4,7,8,11,13,16,22,23] PP GF20; PP/LDPE blends; PP + GF + Talc; PP-TPU; PP CF20; PP CF30; PP + EPDM + TALC 2.4-4.0 [6,9,15,17] PA66 GF 30 1.5-4.0 [7,24] PLA/PHBV; PLA/PTFE (fibril) 3.3-4.0 [10,12] PC; PC/ABS 1.7-4.0 [14,25] PS 3.0…”
Section: Entry In the Literature Listmentioning
confidence: 99%
“…Llewelyn et al presented in their review article the significant development in different aspects of microcellular injection molding [3]. The obtained foamed parts have less weight, improved impact strength, maintained toughness, and insulating properties [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%